Diagnostic value of angiopoietin-2 in the differentiation of malignant pleural effusions - Taş, Dilaver; Köseler, Alaattin (Journal of Surgery and Medicine, 2019)
Aim: Angiopoietins play an important role in the regulation of inflammation, angiogenesis and increased vascular permeability, which are the main steps in the pathogenesis of malignant pleural effusions (MPEs). The present study investigates the diagnostic value of pleural fluid angiopoietin-2 (Ang-2) levels in the differentiation of malignant pleural effusions from other effusions. Methods: This research was designed as case-control study in a single-center. The study included a total of 66 patients (13 had transudate, 28 had benign exudate and 25 had malignant pleural effusions). The patient group involved 25 patients diagnosed with MPE, based on the criteria of lung cancer and other organ malignancies, and malignant pleural effusion. The control group consisted of 41 patients, 13 with transudate according to the Light criteria and 28 with exudate other than MPE (parapneumonic, tuberculous pleurisy, embolism, etc.). Results: Pleural fluid Ang-2 levels were found to be higher in both the benign and malignant exudates than in the transudative pleural effusions (P=0.001). Pleural fluid Ang-2 levels were higher in the benign exudate group than in the malignant exudate group, although the difference was not statistically significant (P=0.874). A patient with an exudative pleural effusion and a pleural fluid Ang-2 level of higher than 13.84 was found to be 1.87 times more likely to have a malignant pleural effusion. Conclusion: Despite the use of Ang-2 levels in the differentiation of transudative and exudative pleural effusions, the present study found that Ang-2 level cannot be used to differentiate between malignant and benign exudative pleural fluids.